2019
DOI: 10.1038/s41598-019-42039-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanized transplanting with side deep fertilization increases yield and nitrogen use efficiency of rice in Eastern China

Abstract: The application of nitrogen (N) fertilizer deep in soil at the same time as mechanical transplanting of rice seedlings is an effective alternative to conventional broadcasting of fertilizer, but its effects on yields and profitability have not been analysed in detail. Here, we analysed the effects of a side deep application of N fertilizer at transplanting on the N uptake, N use efficiency (NUE), grain yield, and economic profitability of two rice ( Oryza sativa L.) cultivars; Yongxian15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Previous field studies showed that deep fertilizer placement, compared to broadcast application, increased yields, improved NUE, and decreased N runoff (Mengel et al 1982;Kelley and Sweeney 2007;Xia et al 2016;Zhu et al 2019). Regarding N 2 O emissions, however, results are rather contradicting: while deep N fertilizer placement effectively lowered N 2 O emissions in rice paddies (Gaihre et al 2015;Wu et al 2017) and field experiments comparing conservation tillage methods (Liu et al 2006;Nash et al 2012), other studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous field studies showed that deep fertilizer placement, compared to broadcast application, increased yields, improved NUE, and decreased N runoff (Mengel et al 1982;Kelley and Sweeney 2007;Xia et al 2016;Zhu et al 2019). Regarding N 2 O emissions, however, results are rather contradicting: while deep N fertilizer placement effectively lowered N 2 O emissions in rice paddies (Gaihre et al 2015;Wu et al 2017) and field experiments comparing conservation tillage methods (Liu et al 2006;Nash et al 2012), other studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient application forms the basis for yield formation and are signi cantly affected by the fertilization mode. Some studies have found that deep fertilization could refer to rice nitrogen use e ciency by increasing the total N content of rice (Zhu et al, 2019). Moreover, the application of fertilizers enhances N, P, K uptake in rice as previously reported (Qiao et al, 2011).…”
Section: Effects Of Deep N Fertilization On Nutrient Accumulationmentioning
confidence: 57%
“…Potassium fertilizer was split-applied with 50% as a basal level and 50% at the panicle initiation stage at a rate of 280 kg·ha −1 potassium. The deep fertilization machine used was developed by the Jinhe Agricultural Science and Technology Co, Ltd. (Zhejiang, China) following the methodology of Zhu 20 . The depth of fertilization was 5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Ten plant hills were sampled from each plot based on the average tiller number at the panicle initiation, heading and maturity stages. To determine level of dry matter accumulation, the sampled plants were dried at 105 °C for 30 min and then dried to a constant weight at 80 °C following the method of Zhu 20 . Panicles, leaves, and stems with leaf sheaths were separated from the plants after the heading stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation